Analyzing social distancing policy effectiveness using Computational Fluid Dynamics inside a bus to prevent COVID-19 airborne transmission. Issue 1 (April 2021) - Pavansai, A.; Deepak, P.; Ragul Hari, S.; Harish, R.; Shyam Kumar, M.B.
Abstract: Coronavirus disease (COVID-19) is a kind of disease that transmits from one body to another through air by the moist particles caused during sneezing and coughing. As a result, to reduce the virus spreading accordingly, 1.83 m of social distancing has been advised to be followed among the humans. Also, it is not well studied that whether the ambient wind and relative humidity (RH) will cause COVID-19 laden cough droplets to transport farther in the air, and make the current social distancing practice ineffective. In this study, computational fluid dynamics simulations are carried out to analyze the transient transport, condensation/evaporation, and deposition of COVID laden droplets emitted by coughs, with the different environmental conditions, cough velocities and Relative Humidity using the developed bus model of size 12 m x 3.5 m x 3.2 m. Different conditions of sneezing and coughing from the human's i.e., the laminar and the turbulent flows of the laden droplets in the air inside the bus were also examined. The distance between the two virtual humans is set as 6 m for a 12 m bus length in order to track the distance covered by cough particles. The facial covering effect on reducing the airborne transmission of the cough droplets has also been evaluated. It is found that due to the ambient air and humidity, the generation of secondary laden droplets occur which travels far and accumulates on the ground or any other third human being around and causes a strong potential risk to their health. The secondary droplets are transforming into large droplets due to high humidity and the hygroscopic effect is evaluated. The 6 feet social distancing is found to be ineffective for halting the spread of viruses among human beings because the micro-laden droplets caused during the sneezing and coughing are influenced by the convection effects and transport from one body to another within 5 s. It is thus recommended to wear masks for both infected and healthy humans to reduce the airborne cough droplets.